Use of Hg-Electroplated-Pt Ultramicroelectrode for Determining Elemental Sulphur in Naphtha Samples - Carlos Eduardo de Andrade; Flávia C. de Souza; Daniella R. Fernandes; Sérgio A. S. Machado; Eliane D'Elia (Journal of Analytical Methods in Chemistry, 2012)
This paper describes the applicability of a Hg-electroplated-Pt ultramicroelectrode in the quantification of elemental sulphur in naphtha samples by square-wave voltammetry. A reproducible deposition methodology was studied and is reported in this paper. This methodology is innovative and relies on the quality of the mercury stock solution to obtain reproducible surfaces required for the analytical methodology. All analyses were performed using a Hg-electroplated-Pt ultramicroelectrode (Hg-Pt UME) due to the low sensibility of such devices to ohmic drops in resistive solutions. The responses of the peak areas in voltammetric experiments were linear in all of the range studied. The method developed here is accurate and reproducible, with a detection limit of 0.010 mg L−1 and a good recovery range for both standard solutions of elemental sulphur (85 to 99%) and real naphtha sample (79%). These results attest to the potential for the application of this electroanalytical methodology in determining elemental sulphur in naphtha samples containing mercaptans and disulphides.